Equitable access to capable teachers: The states respond - Sykes, Gary; Martin, Kacy (Education Policy Analysis Archives, 2019)
This study examined a sample of plans that states submitted to the U.S. Education Department in 2015, pursuant to requirements in the Elementary and Secondary Education Act Title I, Part A. Plans were aimed at redressing inequities in access to qualified teachers as this problem has emerged in states and districts across the country. A considerable body of research has demonstrated that teachers are inequitably distributed to the disadvantage of low income and historically under-served students. Based on descriptive and inferential coding of these plans, the study reaches several conclusions. First, the federal planning mandate has served as an impetus for developing state data systems that track teacher distributions. Second, many of the strategies states are proposing are not directly relevant, targeted, or fully committed in terms of resources and implementation. Third, in states with highly rated plans, the strategies address fundamental, underlying conditions while offering a comprehensive range of targeted strategies to improve recruitment, support, and retention of teachers in schools serving concentrations of low income and under-served students. Progress on this issue is underway with much that remains to be done.